1960
DOI: 10.1039/jr9600003827
|View full text |Cite
|
Sign up to set email alerts
|

758. West African timbers. Part III. Petroleum extracts from the genus Entandrophragma

Abstract: As part of a phytochemical survey of the family Meliaceae, heartwood timber of the four species of the W7est African genus Entandrophragma has been examined. Light-petroleum extraction of all gave " @ "-sitosterol, and four new and apparently related substances have been isolated. The distribution of these within the genus is described.THE relation of plant chemistry to phylogeny has attracted interest for many years.lY2 The heartwood chemistry of the broad-leaved trees of the division Angiospermae has, except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…The charcoal meal test, allows for comparative evaluation of the degree of inhibition or stimulation of gastrointestinal mobility in laboratory animals. 15) Our findings showed that methyl angolensate reduced gastrointestinal transit in mice agreeing with some of the results of in vitro studies in which the extract relaxed the gastrointestinal smooth muscles. It is therefore possible that these properties of methyl angolensate may contribute to the overall effects of the plant in humans.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The charcoal meal test, allows for comparative evaluation of the degree of inhibition or stimulation of gastrointestinal mobility in laboratory animals. 15) Our findings showed that methyl angolensate reduced gastrointestinal transit in mice agreeing with some of the results of in vitro studies in which the extract relaxed the gastrointestinal smooth muscles. It is therefore possible that these properties of methyl angolensate may contribute to the overall effects of the plant in humans.…”
Section: Discussionsupporting
confidence: 79%
“…15) There are no reports in the literature on the direct effects of methyl angolensate on the gastrointestinal smooth muscles and gastrointestinal transit time in mice. In this report, we present the results of the effects of methyl angolensate on these isolated smooth muscle preparations and suggest a possible mechanism of action.…”
mentioning
confidence: 99%
“…The limonoids gedunin (Akisanya et al, 1960) and the ring B-seco methyl angolensate (Bevan et al, 1967) were previously isolated from the stem and root extracts of E. angolense thus giving a clear distinction from the protolimonoids entandrolide, contained in the seeds, and these new, identified in the leaves. Our investigation of a Nigerian specimen of E. angolense, also suggests a chemotaxonomic differentiation within this genus.…”
Section: Resultsmentioning
confidence: 99%
“…E. angolense is used in Western Nigeria as an antimalarial and as an antiulcer (Njar et al, 1995) in ethnomedicine. The meliacins (limonoids) hitherto isolated from E. angolense are gedunin (Akisanya et al, 1960) and methyl angolensate (Bevan et al, 1967) from the stem wood and bark as well as from the root (Orisadipe et al, unpublished work). Gedunin has been shown in vitro to possess antimalarial activities (Bray et al, 1990;MacKinnon et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…There has been no change in the general opinion of Pharmacology & Toxicology that for ethical reasons LD50 should not be used to document effects (Letter from the Editor 1995Editor & 1997Svendsen et al 1997;Notice to contributors 2002 have recently been reported (Orisadipe et al 2000). Other compounds isolated from E.angolense include entandrolide (Okorie & Taylor 1977), gedunin and b-sitosterol (Akisanya et al 1960). There are no reports in literature on the behavioural effects of methyl angolensate so we decided to study the behavioural effects of methyl angolensate on spontaneous motor activity, exploratory activity, pentobarbital induced sleep, amphetamine-induced stereotype behaviour and apomorphine-induced climbing in mice.…”
mentioning
confidence: 99%